Stimuli-Responsive, Shape-Transforming Nanostructured Particles - Lee, Junhyuk; Ku, Kang Hee; Kim, Mingoo; Shin, Jae Man; Han, Junghun; Park, Chan Ho; Yi, Gi-Ra; Jang, Se Gyu; Kim, Bumjoon J. (WILEY-V C H VERLAG GMBH, 2017)
Development of particles that change shape in response to external stimuli has been a long-thought goal for producing bioinspired, smart materials. Herein, the temperature-driven transformation of the shape and morphology of polymer particles composed of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) block copolymers (BCPs) and temperature-responsive poly-(N-isopropylacrylamide) (PNIPAM) surfactants is reported. PNIPAM acts as a temperature-responsive surfactant with two important roles. First, PNIPAM stabilizes oil-in-water droplets as a P4VP-selective surfactant, creating a nearly neutral interface between the PS and P4VP domains together with cetyltrimethylammonium bromide, a PS-selective surfactant, to form anisotropic PS-b-P4VP particles (i.e., convex lenses and ellipsoids). More importantly, the temperature-directed positioning of PNIPAM depending on its solubility determines the overall particle shape. Ellipsoidal particles are produced above the critical temperature, whereas convex lens-shaped particles are obtained below the critical temperature. Interestingly, given that the temperature at which particle shape change occurs depends solely on the lower critical solution temperature (LCST) of the polymer surfactants, facile tuning of the transition temperature is realized by employing other PNIPAM derivatives with different LCSTs. Furthermore, reversible transformations between different shapes of PS-b-P4VP particles are successfully demonstrated using a solvent-adsorption annealing with chloroform, suggesting great promise of these particles for sensing, smart coating, and drug delivery applications.
Keywords: BLOCK-COPOLYMER NANOPARTICLES; GRAPHENE QUANTUM DOTS; SPIN-LABELED POLYMERS; PHASE-TRANSITION; COLLOIDAL PARTICLES; DIBLOCK COPOLYMERS; PHOTONIC CRYSTALS; DRUG-DELIVERY; PH SENSOR; SURFACTANTS